How Demographic Characteristics Shape Risk Tolerance: A Study of Individual Investors in Nepal (The Lumbini Journal of Business and Economics, 2025)
Purpose: This study aims to explore how demographic characteristics influence the risk tolerance behavior of individual investors in Nepal’s stock market. Specifically, it examines how factors such as gender, age, education, occupation, and family wealth shape investors’ willingness to take financial risks.Methods: The research employed a descriptive approach. Data were collected through a structured questionnaire from 390 respondents in Rupandehi District, a growing financial hub in Nepal. The collected responses were analyzed using descriptive statistics, independent t-tests, and one-way ANOVA to analyze differences in risk tolerance across demographic groups.Results: The findings suggest no significant difference between gender and risk tolerance; however, risk tolerance increases with age, older investors are more willing to take risks than younger ones. Education also plays a role, with more educated individuals showing higher risk tolerance but the occupation found to have no effect. Lastly, wealthier investors tend to take more risks, but this effect levels off once family wealth exceeds NPR 250 million, suggesting a limit to how much wealth influences risk-taking.Conclusion: In conclusion, age, education and wealth significantly shape investors’ risk behavior in Nepal. These insights imply that financial advisors and policymakers should customize investment strategies and education programs based on demographic differences to better support individual investors.